PENERAPAN MODEL KOOPERATIF TIPE QUANTUM TEACHING BERBASIS MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR PADA SISWA KELAS IV SD/MI - Syahidan Nurdin, Hurul Ramadhina; Syahidan Nurdin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student learning outcomes in IPAS (Natural and Social Sciences), particularly on magnetic force, among fourth-grade students at SD Negeri Samahani remain low. Most students had not yet reached the Learning Objective Mastery Criteria (KKTP) and required remedial learning. This condition was attributed to teacher-centered instruction, low student engagement, and unengaging media, resulting in a passive, monotonous atmosphere. This study aims to describe the implementation of the cooperative Quantum Teaching model based on interactive multimedia and how the learning process and student outcomes developed afterward. It used a Classroom Action Research (CAR) approach based on the Kurt Lewin model, conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through classroom observation, field notes, teacher interviews, documentation, and learning tests, then analyzed qualitatively through data reduction, display, and conclusion drawing/verification. The findings show the classroom learning process became progressively more student-centered and interactive across the two cycles. In Cycle I, students were largely passive, hesitant to ask questions, and dependent on the teacher's explanation, whereas in Cycle II, they engaged more actively in group discussions, demonstrations, and hands-on activities with real magnets and interactive multimedia, and were noticeably more confident expressing their ideas. This shift was accompanied by a marked improvement in learning outcomes, with far more students meeting the Learning Objective Mastery Criteria by the end of Cycle II. These findings demonstrate that the cooperative Quantum Teaching model based on interactive multimedia effectively improves the learning process and outcomes of elementary school students in IPAS.